Acute Respiratory Infections in Hajj Pilgrims - Audris, Mohamad Ahnaf; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2024)
The Hajj pilgrimage brings millions of Muslims together from various countries, creating a high-risk environment for the spread of infectious diseases, particularly acute respiratory infections (ARI). This study examines ARI risk factors among pilgrims, focusing on a case study at the Surabaya Hajj Dormitory during the 2024 disembarkation period. Data were gathered through temperature checks, swab tests, and assessments of pilgrims showing fever and respiratory symptoms. The results indicate a high prevalence of ARI symptoms among pilgrims, with key risk factors including advanced age, pre-existing health conditions, and high crowd density during rituals. Routine identification and monitoring throughout the disembarkation process can help reduce transmission risks and improve health outcomes for pilgrims. Compliance with mask-wearing, especially among elderly, remains low despite health education efforts. Therefore, preventive measures such as mask distribution and vaccination need to be reinforced to minimize infection risks during Hajj, one of the world’s largest mass gatherings. The government is encouraged to provide adequate healthcare facilities against the spread of infectious diseases.